Echocardiographic reference ranges for normal left atrial function parameters: results from the EACVI NORRE study. (23rd February 2018) - Sugimoto, Tadafumi; Robinet, Sébastien; Dulgheru, Raluca; Bernard, Anne; Ilardi, Federica; Contu, Laura; Addetia, Karima; Caballero, Luis; Kacharava, George; Athanassopoulos, George D; Barone, Daniele; Baroni, Monica; et al.
Abstract: Aims: To obtain the normal ranges for echocardiographic measurements of left atrial (LA) function from a large group of healthy volunteers accounting for age and gender. Methods and results: A total of 371 (median age 45 years) healthy subjects were enrolled at 22 collaborating institutions collaborating in the Normal Reference Ranges for Echocardiography (NORRE) study of the European Association of Cardiovascular Imaging (EACVI). Left atrial data sets were analysed with a vendor-independent software (VIS) package allowing homogeneous measurements irrespective of the echocardiographic equipment used to acquire data sets. The lowest expected values of LA function were 26.1%, 48.7%, and 41.4% for left atrial strain (LAS), 2D left atrial emptying fraction (LAEF), and 3D LAEF (reservoir function); 7.7%, 24.2%, and −0.53/s for LAS-active, LAEF-active, and LA strain rate during LA contraction (SRa) (pump function) and 12.0% and 21.6% for LAS-passive and LAEF-passive (conduit function). Left atrial reservoir and conduit function were decreased with age while pump function was increased. All indices of reservoir function and all LA strains had no difference in both gender and vendor. However, inter-vendor differences were observed in LA SRa despite the use of VIS. Conclusion: The NORRE study provides contemporary, applicable echocardiographic reference ranges for LA function. Our data highlight the importance of age-specific reference values for LA functions.